2020
DOI: 10.3389/fnmol.2019.00314
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Role of TLR-MyD88 Signaling in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a neuro-autoimmune and neurodegenerative disorder leading to chronic inflammation, demyelination, axonal, and neuronal loss in the central nervous system (CNS). Despite intense research efforts, the pathogenesis of MS still remains unclear. Toll-like receptors (TLRs) are a family of type I transmembrane receptors that play a crucial role in the innate immune response. Myeloid differentiation factor 88 (MyD88) is the adaptor of major TLRs. It has been widely considered that the TLR-My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
63
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 124 publications
1
63
0
1
Order By: Relevance
“…We have shown that activation of the Fc receptor of mononuclear cells by ssRNA40/LyoVec was stronger compared to the stimulating effect of LPS, possibly related to the involvement of a subpopulation of "non-classical" monocytes in phagocytosis. Clarification of the role of peripheral blood monocytes in the pathogenesis of the disease, determination of appropriate immunophenotypes, according to some researchers may be of practical importance, in particular to be one of the criteria for predicting the effectiveness of therapy for stratification of patients with multiple sclerosis [4,7,9,18,19]. Zheng S. et al have found out that the dysregulation of TLR7/8 signals on mononuclear cells may be considered as one of the key factors in the development of neuroinflammation in multiple sclerosis [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that activation of the Fc receptor of mononuclear cells by ssRNA40/LyoVec was stronger compared to the stimulating effect of LPS, possibly related to the involvement of a subpopulation of "non-classical" monocytes in phagocytosis. Clarification of the role of peripheral blood monocytes in the pathogenesis of the disease, determination of appropriate immunophenotypes, according to some researchers may be of practical importance, in particular to be one of the criteria for predicting the effectiveness of therapy for stratification of patients with multiple sclerosis [4,7,9,18,19]. Zheng S. et al have found out that the dysregulation of TLR7/8 signals on mononuclear cells may be considered as one of the key factors in the development of neuroinflammation in multiple sclerosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…Clarification of the role of peripheral blood monocytes in the pathogenesis of the disease, determination of appropriate immunophenotypes, according to some researchers may be of practical importance, in particular to be one of the criteria for predicting the effectiveness of therapy for stratification of patients with multiple sclerosis [4,7,9,18,19]. Zheng S. et al have found out that the dysregulation of TLR7/8 signals on mononuclear cells may be considered as one of the key factors in the development of neuroinflammation in multiple sclerosis [7]. Hurtado-Guerrero I. et al have demonstrated that TLR7 signaling mechanisms are disturbed in peripheral blood monocytes in patients with recurrent remitting disease [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TLR adaptor molecules signal through the IKK□/TBK1 complex and the IKKα/IKKβ/IKKγ complex similarly may also involve IRAK-1/IRAK4/TRAF6 complex to activate the transcription factors including IRF3, IRF7, and NF-κBthat ultimately activate IFNs and produces proinflammatory cytokines(Pobezinskaya et al 2008, Ermolaeva MA et al 2008). Previous in vivo study postulates that TLRs signaling programmed by MyD88 adaptor protein and in mice model study reveals the potential involvement of TLR3/TLR4 on SARS-CoV infection(Zheng et al 2020, Perales et al 2013). The study documented that transgenic mice deficient in the TLR3/TLR4 adaptor TRIF are highly susceptible to SARS-CoV infection, showing increased weight loss, mortality, reduced lung function, increased lung pathology, and higher viral titers.…”
Section: Discussionmentioning
confidence: 99%